Ultrasound-guided percutaneous release procedures in the transverse carpal ligament by acupotomy: A cadaveric study - Zhou, Qiaoyin; Shen, Yifeng; Zhu, Xinyue; Sun, Xiaojie; Qiu, Zuyun; Li, Shiliang; Zhang, Weiguang (Frontiers in Surgery, 2023)
Objective This study aimed to determine the safety and accuracy of ultrasound-guided acupotomy percutaneous loosening of the transverse carpal ligament. Methods The 100 upper limb specimens were equally divided into the ultrasound-guided acupotomy group (U) and the nonultrasound-guided acupotomy group (N). For the U group, we simulated ultrasound-guided acupotomy loosening of the transverse carpal ligament in a human specimen, and for the N group, we performed the loosening of the transverse carpal ligament through the same approach under nonultrasound-guided conditions. The safety and accuracy of the two methods were compared through measurement. Results In the ultrasound-guided group, the injury rate of nerves, blood vessels and tendons caused by needle-knife release was 0%. In the non-ultrasound-guided group, the rate of nerve, blood vessel and tendon damage was 6 percent, 12 percent and 20 percent, respectively. χ2 test (Fisher exact test) was performed for the nerve and blood vessel damage rates in the two groups (PN > 0.05, PA < 0.05), the difference in nerve damage rates was not statistically significant, but the difference in blood vessel damage rates was statistically significant. Pearson's χ2 test was performed on the tendon injury rates of the two groups (PF < 0.05), and the difference was statistically significant. In the ultrasound-guided group, the proportion of acupotomy marks greater than or equal to half of the width of the transverse carpal ligament was 86%, and the non-ultrasound-guided group was 36%. The accuracy of the two surgical methods was tested by Pearson's χ2 test (PL < 0.05), and the difference was statistically significant. According to the measurement, the ultrasound-guided acupotomy technology had high safety and accuracy. Conclusion In this study, we designed a new method for cutting the transverse carpal ligament under ultrasound guidance, which is different from surgery. These results indicate that this is a safe and accurate method of interventional treatment of carpal tunnel syndrome.